Remote Ischemic Preconditioning: A Novel Strategy in Rescuing Older Livers From Ischemia-reperfusion Injury in a Rodent Model. Issue 5 (November 2016) - Limani, Perparim; Linecker, Michael; Oberkofler, Christian E.; Barmettler, Gery; Kaech, Andres; Graf, Rolf; Humar, Bostjan; Clavien, Pierre-Alain
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The aim of this study was to determine whether remote ischemic preconditioning (RIPC) protects aged liver against ischemia reperfusion (IR). Summary of Background Data: The demands for liver surgery in an aging population are growing. Clamping of vessels to prevent blood loss is integral to liver surgery, but the resulting IR injury (IRI) augments postoperative complications. More so, sensitivity to hepatic IRI increases with age; however, no strategies have been developed that specifically protect old liver. RIPC, a novel protective approach, was performed distant to the surgical site. Whether RIPC may also protect old liver from IRI is unknown. Methods: RIPC to the femoral vascular bundle was compared against direct ischemic preconditioning (IPC) and the standard of care intermittent clamping (IC) using a model of partial hepatic ischemia in mice aged 20 to 24 months. Liver injury was measured 6 hours after reperfusion. Protective signaling (serotonin-Vegf-Il10/Mmp8 axis, Kupffer cell polarization) was assessed immediately after preconditioning. Neutralizing antibody was used to test the role of Vegf. Hepatic vasculature was examined by electron microscopy. Results: RIPC was superior over other strategies in protecting old liver from IRI, with standard IPC approaches being ineffective. RIPC induced the strongest elevations in circulating Vegf, and Vegf inhibition dampened protective signaling and abrogated the protective effects. RIPC was further associated with improvements in vascular functionality. Conclusions: RIPC is highly effective in protecting old liver from ischemic insults, mainly owing to its ability to induce circulating Vegf. These findings warrant efforts toward clinical translation.